Опасный младенец: [роман] / Елена Басманова - Басманова Елена (Русский проект, 2002)
Экземпляры: (20180627) / Инвентарный номер: 40658 / Цена: 31.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 27 / ББК: 84(2Рос=Рус)6